MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK TERPADU MELALUI PENDEKATAN SAINTIFIK - Ridlo, Hasyim Taufiq; Abdurakhman, Omon; Pradana, Yudha (Universitas Djuanda, 2015)
Application of Scientific approach can increase student motivation in an integrated thematic learning. In the classroom experiments using the scientific approach, while learning in the control group using the cookbook approach. The research proves that the scientific approach is more effective than the cookbook approach, with the end result, the class Experiment (Observing = 90, 24%; Questioning = 89.88%; Experiment = 87.56%; Associating = 90, 12%; Communicating = 90.00%) mean = 90.00%. While the control class (Observing = 64, 05%; Questioning = 61.90%; Experiment = 70, 12%; Associating = 63.57%; Communicating = 55.60%) Mean = 63.05%. And the results of questionnaires received 39.64% with a high motivation criteria. Application of Scientific approach can improve student learning outcomes in an integrated thematic learning, it is evident from the results of the research, with the result: 89.02 posttest than the pretest 55.24 (up 0.72%), with excellent results or above KKM is 75 %; 2.66. While in the control class are 0.58% of the value of the initial value (pretest = 52.86% and 63.10% posttest =, with the results of the control class has not met the minimum criteria of KKM. With the above results that the Application of Scientific approach is more effective in learning to enhance the Learning Motivation and Students Learning Outcomes in class II of SDN Tugu 10 Cimanggis Depok.